2015
DOI: 10.5897/ijwree2014.0558
|View full text |Cite
|
Sign up to set email alerts
|

Water planning and management in sustainable new town building, the case of Ramshar

Abstract: The focus of this paper is on new town building in hydro drought regions. It looks at new town building from the sustainability perspective; especially it discusses the supply and distribution of water in the new towns. The aim of this paper is to resolve a dilemma in the arid regions. One side a much demand for new towns because of the population growth and other side the water anxiety is being a key reason hindering the urban development. Methodological approaches of this paper is to supply some volumes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Untreated urban wastewater spread Covid-19 disease. We recognized the importance of supplying qualified water for built environments and collecting and treating urban wastewaters [17,18]. Studies suggested that Coronavirus existed in the wastewaters [19,20].…”
Section: Field Studies and Experiencesmentioning
confidence: 99%
“…Untreated urban wastewater spread Covid-19 disease. We recognized the importance of supplying qualified water for built environments and collecting and treating urban wastewaters [17,18]. Studies suggested that Coronavirus existed in the wastewaters [19,20].…”
Section: Field Studies and Experiencesmentioning
confidence: 99%